Angiopoietin-1 enhances skeletal muscle regeneration in mice - Mofarrahi, Mahroo (Am J Physiol Regul Integr Comp Physiol, 2015)
Activation of muscle progenitor cell myogenesis and endothelial cell angiogenesis is critical for the recovery of skeletal muscle from injury. Angiopoietin-1 (Ang-1), a ligand of Tie-2 receptors, enhances angiogenesis and skeletal muscle satellite cell survival; however, its role in skeletal muscle regeneration after injury is unknown. We assessed the effects of Ang-1 on fiber regeneration, myogenesis, and angiogenesis in injured skeletal muscle (tibialis anterior, TA) in mice. We also assessed endogenous Ang-1 levels and localization in intact and injured TA muscles. TA fiber injury was triggered by cardiotoxin injection. Endogenous Ang-1 mRNA levels immediately decreased in response to cardiotoxin then increased during the 2 wk. Ang-1 protein was expressed in satellite cells, both in noninjured and recovering TA muscles. Positive Ang-1 staining was present in blood vessels but not in nerve fibers. Four days after the initiation of injury, injection of adenoviral Ang-1 into injured muscles resulted in significant increases in in situ TA muscle contractility, muscle fiber regeneration, and capillary density. In cultured human skeletal myoblasts, recombinant Ang-1 protein increased survival, proliferation, migration, and differentiation into myotubes. The latter effect was associated with significant upregulation of the expression of the myogenic regulatory factors MyoD and Myogenin and certain genes involved in cell cycle regulation. We conclude that Ang-1 strongly enhances skeletal muscle regeneration in response to fiber injury and that this effect is mediated through induction of the myogenesis program in muscle progenitor cells and the angiogenesis program in endothelial cells.